Impact of age on efficacy and toxicity of nilotinib in patients with chronic myeloid leukemia in chronic phase: ENEST1st subanalysis - Giles, Francis J.; Saußele, Susanne (Journal of cancer research and clinical oncology, 2017)
Purpose: Achievement of deep molecular response with a tyrosine kinase inhibitor in patients with chronic myeloid leukemia (CML) is required to attempt discontinuation of therapy in these patients. The current subanalysis from the Evaluating Nilotinib Efficacy and Safety in Clinical Trials as First-Line Treatment (ENEST1st) study evaluated whether age has an impact on the achievement of deeper molecular responses or safety with frontline nilotinib in patients with CML. Methods: ENEST1st is an open-label, multicenter, single-arm, prospective study of nilotinib 300 mg twice daily in patients with newly diagnosed CML in chronic phase. The patients were stratified into the following 4 groups based on age: young (18-39 years), middle age (40-59 years), elderly (60-74 years), and old (≥75 years). The primary end point was the rate of molecular response 4 ([MR4] BCR-ABL1 ≤0.01% on the international scale) at 18 months from the initiation of nilotinib. Results: Of the 1091 patients enrolled, 1089 were considered in the analysis, of whom, 23% (n = 243), 45% (n = 494), 27% (n = 300), and 5% (n = 52) were categorized as young, middle age, elderly, and old, respectively. At 18 months, the rates of MR4 were 33.9% (95% confidence interval [CI], 27.8-40.0%) in the young, 39.6% (95% CI, 35.3-44.0%) in the middle-aged, 40.5% (95% CI, 34.8-46.1%) in the elderly, and 35.4% (95% CI, 21.9-48.9%) in the old patients. Although the incidence of adverse events was slightly different, no new specific safety signals were observed across the 4 age groups. Conclusions: This subanalysis of the ENEST1st study showed that age did not have a relevant impact on the deep molecular response rates associated with nilotinib therapy in newly diagnosed patients with CML and eventually on the eligibility of the patients to attempt treatment discontinuation.
Gesehen am 04.07.2018